2007
DOI: 10.1183/09031936.00014107
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke condensate inhibits ENaC α-subunit expression in lung epithelial cells

Abstract: Cigarette smoke has been associated with lung fluid accumulation and increased risk of acute respiratory distress syndrome. It was postulated that ENaC a-subunit, which plays a critical role in lung fluid absorption, is affected by cigarette smoke.Cigarette smoke condensate (CSC) was used to treat a human lung epithelial cell line. ENaC a-subunit expression was measured using immunoblotting, quantitative PCR and promoterreporter assays.The current authors found that CSC, without affecting cell survival, suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In the current study, two cell lines were included to permit assessing effects at various transformational stages and to meet the need to examine results in more than one cell line. The CSC dose range used, although difficult to compare with that in human airways in smokers, is similar to those previously reported in other in vitro studies (0 – 125 μg/ml) [23-26]. Additionally, the average yield of CSC was 26.1 mg/cigarette.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In the current study, two cell lines were included to permit assessing effects at various transformational stages and to meet the need to examine results in more than one cell line. The CSC dose range used, although difficult to compare with that in human airways in smokers, is similar to those previously reported in other in vitro studies (0 – 125 μg/ml) [23-26]. Additionally, the average yield of CSC was 26.1 mg/cigarette.…”
Section: Resultssupporting
confidence: 70%
“…CSC is widely used in model systems to study in vitro effects of tobacco smoke [23-26]. A disadvantage is that cell culture models often do not exhibit all the differentiated and functional characteristics of the corresponding native epithelium or the entire organ.…”
Section: Resultsmentioning
confidence: 99%
“…By using both H441 and Calu-3 cells, we show that this inhibition is present in more than one cell line with well-preserved lung epithelial characteristics. H 2 O 2 -induced changes in ␣-subunit variants were not detected in HAE cells (32), suggesting that the response to H 2 O 2 could be cell line-dependent. The finding that H 2 O 2 inhibits ␣-subunit expression in H441 and Calu-3 cells will help us in the evaluation of cell physiology data derived from H441 and Calu-3 monolayers under oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…Studies in human subjects and animal models have demonstrated that asymptomatic smokers have significantly greater lung epithelial permeability, a pathophysiological hallmark of ALI, as compared with nonsmokers (7-10). Active smoking also decreases expression of the primary ion channels responsible for resolving alveolar edema, which could impair alveolar fluid clearance and thus increase formation of lung edema (38,39). Likewise, both endothelial injury and disordered platelet function are thought to be critical to the pathogenesis of ALI (40,41), and the cardiovascular literature has demonstrated the potent effects of both active and secondhand smoke on both of these processes (16).…”
Section: Discussionmentioning
confidence: 99%